"Modern Ways of Development of the Food Industry in the Republic of Karakalpakstan" (Eurasian Research Bulletin, 2022)
Undoubtedly, the food business is undergoing a dynamic transformation as a result of its ongoing expansion in an effort to meet demand and address major issues brought on by the constantly expanding supply of food, both in terms of quantity and quality. In this regard, it is essential to assess technical developments and trends that will alter how the public views the food sector, emphasizing the most recent needs for equipment functionality. This article looks closely at the state of the food business and, in particular, analyzes how contemporary methods are being used to produce food in the Republic of Karakalpakstan